Divine Providence, Divine Hiddenness, and Commitment to the Good - Di Ceglie, Roberto (TheoLogica: An International Journal for Philosophy of Religion and Philosophical Theology, 2022)
Divine providence plays a significant role in John Schellenberg’s formulation of the divine hiddenness argument. Although Schellenberg does not openly mention the providence of God, his refutation of this attribute supports his denial of God’s existence, a denial which is the aim of Schellenberg’s hiddenness argument. In this article, I show that Schellenberg’s implicit refutation of providence presupposes two assumptions, the more comprehensive of which consists in saying that there is no good end of history and no commitment to the good is required on the part of the prospective believer. I argue that the assumptions at stake are inconsistent with Schellenberg’s view of God as the omnipotent, omniscient and perfectly loving creator of all things, a view which Schellenberg uses as a starting point for his hiddenness argument.